The Influence of Simvastatin on NGAL, Matrix Metalloproteinases and Their Tissue Inhibitors in Human Intraluminal Thrombus and Abdominal Aortic Aneurysm Tissue. Issue 5 (May 2015) - Piechota-Polanczyk, A.; Demyanets, S.; Mittlboeck, M.; Hofmann, M.; Domenig, C.M.; Neumayer, C.; Wojta, J.; Klinger, M.; Nanobachvili, J.; Huk, I.
<x xml:space="preserve">Abstract</x> Objective/Background Matrix metalloproteinases (MMPs) play a pivotal role in the development and progression of abdominal aortic aneurysms (AAAs). The action of MMPs depends on a balance between tissue inhibitors of MMPs (TIMPs) and compounds that may prolong protease activity, such as neutrophil gelatinase-associated lipocalin (NGAL). Methods The study was designed to analyse gene expression and protein concentration of MMPs, TIMPs, and NGAL in AAA walls and intraluminal thrombi (ILTs) of patients on simvastatin (n = 10) and not on statins (n = 10). The patients were matched by age, sex, and AAA diameter. Expression of MMP2, MMP9, TIMP1, TIMP2, and NGAL was investigated by real time polymerase chain reaction, and MMP2, MMP9, MMP9/TIMP1, MMP9/TIMP2, and MMP9/NGAL protein levels by enzyme-linked immunosorbent assay. Results MMP2 and MMP9 protein and mRNA levels were comparable in the simvastatin and non-statin groups (p > .05); however, there was a significant decrease in TIMP1 mRNA in AAA tissue (p = .04). Moreover, a significant increase in MMP9/TIMP2 complex concentration in ILTs of patients on simvastatin was noted (median 94.71 ng/mL in the simvastatin group vs. 36.80 ng/mL in the non-statin group; p = .01). No significant difference was observed for NGAL mRNA or protein content in AAA and ILT. Conclusion Simvastatin treatment in patients with AAAs may influence the concentration of proteases and their inhibitors (TIMPs) in aneurysmal wall tissue and ILTs. Thus, further studies should be undertaken to understand the different influence of statin therapy on the components of the MMP/TIMP system in AAAs and ILTs.